Murder in the oval library - Gleason, Colleen (Gleason, Colleen. Lincoln White House mysteries., 2018)
With the Confederate Army firing on Fort Sumter, the Civil War has begun<U+2014>and an invasion of Washington, DC, from Secessionist Virginia seems imminent. As the population evacuates, the President is in desperate need of men to defend the capital. Lincoln<U+2019>s trusted aide, Adam Speed Quinn, and Quinn<U+2019>s old friend from the Bloody Kansas conflict, Senator Jim Lane, hastily assemble a motley crew of just over a hundred men and garrison them in the East Room at the White House. Dubbed the Frontier Guard, these rough-and-tumble patriots steel themselves for the inevitable attack. But even as dawn breaks with no Rebel strike, a single act of violence intrudes within the White House. One of the Frontier Guard lies dead in the oval library, throat slit ear to ear. There is a murderer among them. Lincoln promptly assigns Quinn to deal with the matter, who is in turn aided by journalist Sophie Gates and Dr. George Hilton. And to Quinn<U+2019>s chagrin, the Southern belle Constance Lemagne insists on being involved in the investigation as well. But when Dr. Hilton examines the body, he makes a startling discovery that overturns all Quinn<U+2019>s assumptions about the murder. With his president at grave risk from without and within, Quinn must act quickly to catch the White House killer . . .